Identifying patients presenting in pain to the adult emergency department: A binary classification task and description of prevalence. (May 2023) - Hughes, James A; Douglas, Clint; Jones, Lee; Brown, Nathan J.; Nguyen, Anthony; Jarugula, Rajeev; Lyrstedt, Anna-Lisa; Hazelwood, Sarah; Wu, Yutong; Chu, Kevin
Highlights: A retrospective methodology for the identification of patients presenting in pain. The prevalence of pain on arrival to this ED over a three-year period was 55.2%. Pain is identifiable from triage assessments.